Typological study of metal pins in northwestern Iran based on the Bayazid Abad (Bayazi Awa) rchaeological assemblage - Amelirad, Shelir; Khanmohamadi, Behroz (Iran, 2024)
The Bayazid Abad hypogeum has yielded a remarkable assemblage of artefacts, 120 of which were metal pins of various categories, dating from Middle Bronze Age II to Iron Age II. This collection shows a widespread typological affinities with other areas of the Near East. The pins (mostly so-called “toggle pins”) have a strong affinity with the forms which most commonly occur in the Levant and Mesopotamia, which suggests that the use of toggle pins starts in the Middle Bronze Age and persists until the end of the Late Bronze Age. Comparison of the pins dated to Iron I and II shows strong connections with examples from neighbouring sites, although all present uniquely localised forms and details of manufacture.